The association between neuroendocrine/glucose metabolism and clinical outcomes and disease course in different clinical states of bipolar disorders - Zhang, Xu; Zhou, Yaling; Chen, Yuexin; Zhao, Shengnan; Zhou, Bo; Sun, Xueli (Frontiers in Psychiatry, 2024)
Objective: The treatment of bipolar disorder (BD) remains challenging. The study evaluated the impact of the hypothalamic-pituitary-adrenal (HPA) axis / hypothalamic-pituitary-thyroid (HPT) axis and glucose metabolism on the clinical outcomes in patients with bipolar depression (BD-D) and manic bipolar (BD-M) disorders. Methods: The research design involved a longitudinal prospective study. A total of 500 BD patients aged between 18 to 65 years treated in 15 hospitals located in Western China were enrolled in the study. The Young Mania Rating Scale (YMRS) and Montgomery and Asberg Depression Rating Scale (MADRS) were used to assess the BD symptoms. An effective treatment response was defined as a reduction in the symptom score of more than 25% after 12 weeks of treatment. The symptoms score was correlated with the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) index, the HPA axis hormone levels (adrenocorticotropic hormone (ACTH) and cortisol), and the HPT axis hormone levels (thyroid stimulating hormone (TSH), triiodothyronine (T3), thyroxine (T4), free triiodothyronine (fT3) and free thyroxine (fT4)). Results: In the BD-M group, YMRS was positively correlated with baseline T4 (r=0.349, P=0.010) and fT4 (r=0.335, P=0.013) and negatively correlated with fasting insulin (r=−0.289, P=0.013). The pre-treatment HOMA-IR was significantly correlated with adverse course (P=0.045, OR=0.728). In the BD-D group, the baseline MADRS was significantly positively correlated with baseline fT3 (r=0.223, P=0.032) and fT4 (r=0.315, P=0.002), while baseline T3 (P=0.032, OR=5.071) was significantly positively related to treatment response. Conclusion: The HPT axis and glucose metabolism were closely associated with clinical outcomes at 12 weeks in both the BD-D and BD-M groups. If confirmed in further longitudinal studies, the monitoring of T3 in BD-D patients and HOMA-IR for BD-M could be used as potential treatment response biomarkers.